Analisis Multidrug Resistensi Terhadap Antibiotik Pada Salmonella typhi Dengan Teknik Multiplex PCR - Andi Evi Erviani (Biogenesis: Jurnal Ilmiah Biologi, 2013)
This research is about the analysis of resistance multidrug for antibiotic of Salmonella typhi with multiplex technique of PCR. This research purpose conducted to determine the presence of resistance multidrug for kloramfenikol and ampicillin of Salmonella typhi using multiplex technique of PCR. Testing of resistance multidrug performed using disc diffusion test and detection of resistance gene for kloramfenikol (cat P) and ampicillin (tem) with molecular technique using multiplex of PCR. Result of research indicate the suitability between resistance test using disc diffusion and detection resistance gene with multiplex of PCR, which is based on result of disc diffusion test and multiplex of PCR have occurred of resistance multidrug for kloramfenikol and ampicillin antibiotics, amount 10 patients (33.3%), resistance of one antibiotics amount 10 patient (33.3%) and non-resistance (sensitive) for both antibiotic amount 10 patient (33.3%).Keywords: Antibiotics, Multidrug, Resistance, Salmonella typhi